The Social Imaginaries of Women's Peace Activism in Northern Uganda - Chigudu, Simukai (International Feminist Journal of Politics, 2016)
The metanarrative of global feminism is often constructed as a progressive and emancipatory movement emanating from the West and fostering radical politics elsewhere in the world. Such a view is not only ethnocentric but, critically, it fails to engage with the complex ways in which feminist politics travel and are evinced in specific localities. In this article, I seek to understand how marginalized women in the “Global South” – particularly in Africa – interpret, experience and negotiate feminist ideas to wield political power within the context of their social and moral worlds. I focus on women's organized resistance to violence and armed conflict, known as “women's peace activism.” Using a case study of a women's peace movement in Uganda mediated by an international feminist organization called Isis Women's International Cross-Cultural Exchange, I conducted in-depth qualitative interviews with a wide range of activists in the organization and in its network in postconflict areas in Northern Uganda. I argue that the feminist peace discourse is most meaningful when its universal values of equity and securing the dignity of women are appropriated and re-signified through the cultural institutions and the collective memory of activists in their local settings.
Keywords: feminism, violence and peacebuilding, transnational politics, Uganda, social imaginaries